2011
DOI: 10.1111/j.1467-9299.2010.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Local Governance: Institutional Forms of Collaboration

Abstract: The article discusses institutional forms of governance, understanding governance as hybrid forms of collaboration, involving government, market actors and/or civil society actors. By utilizing data from a study made of three Norwegian cities, six collaborative efforts are presented, and discussed in relation to analytical characteristics derived from both network theory and organizational theory. This analysis illustrates that these collaboration efforts can, on the one hand, be understood as something locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
(18 reference statements)
0
30
0
Order By: Relevance
“…While we have limited this study to discussion of effects of MOCs, there exists a body of literature Gradus, Elbert Dijkgraaf, and Wassenaar 2014;Rodrigues, Tavares, and De Araújo 2012;Røiseland 2011;Tavares and Camões 2007) examining the causes of MOCs. Moreover, we did not discuss (chapters in) books and publications in other sources than peer-reviewed academic journals, which increased our study's reliability at the expense of its sample size.…”
Section: Discussionmentioning
confidence: 99%
“…While we have limited this study to discussion of effects of MOCs, there exists a body of literature Gradus, Elbert Dijkgraaf, and Wassenaar 2014;Rodrigues, Tavares, and De Araújo 2012;Røiseland 2011;Tavares and Camões 2007) examining the causes of MOCs. Moreover, we did not discuss (chapters in) books and publications in other sources than peer-reviewed academic journals, which increased our study's reliability at the expense of its sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Goal consensus, joint action and motivation are related to both the degree of factors' agreement about the network's goals and to the strategies implemented to ensure the goals' achievement (Provan and Kenis 2008;Røiseland 2011;Emerson et al 2012 ).…”
Section: Starting Conditionsmentioning
confidence: 99%
“…For example, Vabo and Røiseland (2012) have-through empirical enquires-demonstrated how classic and generic frameworks analyzing tools of government are still relevant in network context, and therefore argue for a bridge between the classical literature on policy instruments and the growing framework of metagovernance. Røiseland(2011) has also elsewhere, based on studies of collaborative arrangements in local government, demonstrated that the institutional forms of such arrangements do in reality exist in a continuum between the archetypical definitions of government and governance from the literature.…”
Section: The Governing Of Governance: Metagovernancementioning
confidence: 99%